Tissue engineering and the challenges of “playing god”: a theological analysis - Hashi, Abdurezak Abdulahi; Ahmad Radzi, Muhammad Aa'zamuddin; Mohd. Azharuddin, Nur Syamimi; Azhim, Azran; Munirah, Sha'ban (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2018)
One of the major scientific modern advances in the field of biosciences is tissue engineering. In the practices of tissue engineering, scientists use of combination of cells, biomaterial scaffolds and signaling factors, to generate new tissues, that can be used to replace diseased or damaged tissues including bones, cartilage, bladder, skin and muscles. In the initial stages of tissue engineering, this field was counted among the subfields of biomaterials, however for it includes various scientific and engineering practices, it gradually become independent field of study with promising outcomes particularly when viewed as a way of regenerative medicine. In these practices, the scientists attempt to generate new cells and tissues cultured in the scientific labs. There are instance in which these practices are equated to “creation of cells”, and thus related scientists are subsequently assumed as “playing gods”, an understanding that poses a far reaching theological and moral challenges to traditional and believing communities. It challenges the fundamental belief held by major religious faiths about the Creator God, Who is the source of life, and the Creator of everything and everyone. While in major religious beliefs, it is only God, Who creates life, scientific practices of tissue engineering and stem cell researches, have in some sense depicted man of science to have a role in the process of reproducing living things. This is so, because, if given tissues and cells can be regenerated in given scientific labs, does that mean creating life? If so, is man of science creating, in other word “playing god”? These types of questions generated tremendous theological and philosophical controversies within the scientific community as well as among religious communities. This paper uses analytical method and aims to study the theological challenges of tissue engineering practices, particularly the issues related to playing God, from and within the Islamic theology. The study illustrates the theological challenges of tissues engineering, and analysis the Muslim theological responses to these debates, with brief comparison to that of other faiths.